In Vitro Synergistic Effect of Curcumin in Combination with Third Generation Cephalosporins against Bacteria Associated with Infectious Diarrhea - Sasidharan, Nishanth Kumar (Hindawi Publishing Corporation, 2014)
Diarrhea is one of the leading causes of morbidity and mortality in humans in developed and developing countries. Furthermore, increased resistance to antibiotics has resulted in serious challenges in the treatment of this infectious disease worldwide. Therefore, there exists a need to develop alternative natural or combination drug therapies. The aim of the present study was to investigate the synergistic effect of curcumin-1 in combination with three antibiotics against five diarrhea causing bacteria. The antibacterial activity of curcumin-1 and antibiotics was assessed by the broth microdilution method, checkerboard dilution test, and time-kill assay. Antimicrobial activity of curcumin-1 was observed against all tested strains. The MICs of curcumin-1 against test bacteria ranged from 125 to 1000 μg/mL. In the checkerboard test, curcumin-1 markedly reduced the MICs of the antibiotics cefaclor, cefodizime, and cefotaxime. Significant synergistic effect was recorded by curcumin-1 in combination with cefotaxime. The toxicity of curcumin-1 with and without antibiotics was tested against foreskin (FS) normal fibroblast and no significant cytotoxicity was observed. From our result it is evident that curcumin-1 enhances the antibiotic potentials against diarrhea causing bacteria in in vitro condition. This study suggested that curcumin-1 in combination with antibiotics could lead to the development of new combination of antibiotics against diarrhea causing bacteria.